Quasi - 3D and Full - 3D Approaches for Numerical Simulation in Axial Flow Hydraulic Turbine - Prasad, Vishnu; Sayann, K. S.; Krishnamachar, P (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Water passes through the rows of stationary and rotating blades in the turbine space and thus the flow becomes complex. The application of computational fluid dynamics (CFD) is steadily increasing to improve design of hydraulic turbines. The numerical flow simulation in the hydraulic turbine space can either be based on potential or viscous flow theory. In both the approaches, detailed flow behavior in complete turbine space is obtained. The quasi- 3D potential flow approach is quick and simple as compared to full-3D viscous flow methods of analysis but do not take into account the friction losses, which need to be computed separately. The direct flow analysis has been carried out in an experimentally tested model of axial flow hydraulic turbine using the two approaches and the comparison of flow pattern and computed parameters in runner is made in present paper. The computed efficiencies and other performance parameters have also been compared with experimental values at some critical points for validation. Hydro Nepal: Journal of Water, Energy and Environment Issue No. 4, January, 2009 Page 42-48